Health technology assessment and comparative effectiveness research: a pharmaceutical industry perspective. (August 2013) - Hao, Yanni; Thomas, Adrian
We briefly review the characteristics of several established health technology assessment (HTA) programs in industrialized societies including Germany, the UK and France. Special attention is paid on two issues: the position of HTA in coverage decision making and the role of economic assessment in evaluation processes. Although law makers in the USA have barred the use of NICE's cost/quality-adjusted life year or similar health economics approaches by public payers for coverage decision making, there are suggestions of prioritizing relative efficacy evaluation over economic assessment under a comparative effectiveness research (CER) framework to inform payment rates of public payers (an approach similar to German and French HTA processes). However, such an approach is unlikely to prove viable. It should also be noted that, if cost considerations are made explicit in US CER policy decisions, CER may become an unsustainable approach undermined by a conflicting emphasis on both cost containment and a demand for costly comparative evidence. On the other hand, properly designed CER initiatives can serve as a facilitator of more efficient research activities and drug development models. With these points in mind, the likely pathway of US CER is explored and the plausible impact on industry innovation is discussed.